2019
DOI: 10.17051/ilkonline.2019.527198
|View full text |Cite
|
Sign up to set email alerts
|

Dokuzuncu Sınıf Öğrencilerinin Fizik Laboratuvarı Malzemelerini Tanıma Düzeyleri

Abstract: Bu araştırmanın amacı, liseye başlayan öğrencilerin önceki okul yaşamlarında fizik laboratuvarında bulunan deney malzemelerini ne derece tanıdıklarını belirlemektir. Araştırma tarama yöntemi ile gerçekleştirilmiştir. Araştırmada, araştırmanın yapıldığı fizik laboratuvarlarında kullanılan ve öğrencilerin tanıması beklenen 28 adet deney malzemesi seçilmiştir. Deney malzemeleri önce öğrencilere gösterilmiş ve incelemeleri istenmiştir. Öğrencilerden kendilerine gösterilen deney malzemesinin adını ve işlevini açık … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Therefore, it is concluded that factual information and functional information are interdependent. Similarly, Kızılcık, et al in their study found a significant relationship between students' knowledge regarding experimental materials correctly and stating their functions correctly [42].…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Therefore, it is concluded that factual information and functional information are interdependent. Similarly, Kızılcık, et al in their study found a significant relationship between students' knowledge regarding experimental materials correctly and stating their functions correctly [42].…”
Section: Discussionmentioning
confidence: 71%
“…Thus, students will not have sufficient applied knowledge regarding the use of laboratories. In this regard, Kızılcık, et al in their study revealed that secondary school students are not able to define physics laboratory materials in general or even to put forward an idea about many materials [42].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Bu sorunları aşabilmek için örnek uygulamalara ihtiyaç duyulmaktadır ve bu tür uygulamalar öğretmen eğitimcilerinin sorumluluğunda olması gerekmektedir (Barak, 2017). Ayrıca öğretmen adaylarının laboratuvar malzemelerini ve araç-gereçlerini daha iyi tanıması ve kullanması konusunda ne gibi yöntemlere başvurmak gerektiği konusunun incelenmesine de gerek duyulmaktadır (Kızılcık, Çağan, & Yavaş, 2019).…”
Section: Laboratuvar Deneyimlerine İlişkin öğRetmen Eğitimiunclassified